Socio-Demographic and Environmental Factors Associated with Motorcycle Accidents: A Study at Nakuru Level 5 Hospital, Kenya - Ngetich, Evans K.; Suge, Valerie; Nyaga, Ann W.; Cherotich, Georgina (Journal of Clinical Care and Medical Advancement, 2025)
Motorcycle accidents currently rank third among the leading causes of injuries resulting from road traffic accidents in Kenyan hospitals. This study aimed to assess the socio-demographic characteristics and perceived environmental factors influencing motorcycle accidents among patients seeking medical care at Nakuru Level 5 Hospital in Kenya. A cross-sectional study design was employed, and structured questionnaires were used to collect data. The study population comprised individuals who had been involved in motorcycle accidents and were seeking treatment at the hospital. The assessment included gathering socio-demographic information, roles played by participants during accidents, and environmental factors present at the time of the accidents. Data analysis was conducted using descriptive statistics. Out of the 150 questionnaires distributed, 136 were completed and returned, resulting in a response rate of 90.67%. The majority of participants fell into the age range of 25 to 29 years (59.23%), and the majority were male (82.96%). Most participants had attained a secondary level of education (51.29%) and had a monthly income ranging from KES 0 to KES 10,000 (52.96%). Furthermore, a significant percentage of the participants were involved in the “Boda Boda” business (89.23%). In terms of their roles during accidents, motorcycle riders accounted for 78.56%, followed by passengers (13.89%). Environmental factors indicated that accidents were more frequent during rainy weather (73.53%) and at night when visibility was impaired (73.53%). Interestingly, the majority of accidents (94.85%) occurred irrespective of the road condition, highlighting the need for improved road infrastructure. In conclusion, this study underscores the susceptibility of young adults, particularly male motorcycle riders, to accidents. It also reveals prevalent factors such as low education levels, low income, and engagement in the “Boda Boda” business among the participants